Stress reduction interventions: A scoping review to explore progress toward use of haptic feedback in virtual reality - Brelet, Lisa; Gaffary, Yoren (Frontiers in Virtual Reality, 2022)
With the objective of providing scientific guidance for the development of a multisensory virtual reality (VR) relaxation device using haptic stimulation, the present review focuses on analysis of existing traditional and VR-based stress reduction interventions as well as their relevant measures. Two primary methods of stress reduction are explored: relaxation techniques and meditation techniques. Relaxation techniques enable the practitioner to achieve a tension-free state through control of and reduction in physiological activity. Meditation techniques also induce a relaxation response, but can additionally increase sustained attention to the present moment, to one’s own bodily sensations, emotions, tensions, thoughts, etc., or to an object, without judgement or adherence to a particular perspective. The limitations of traditional techniques are also noted, including the time required for training or mastery and the need for visualization efforts, and the benefits of VR-based relaxation techniques for the user are explored: these include the reduction of negative emotions, stress, anxiety, depression, and pain, as well as improved relaxation and positive affect. Particular attention is paid to the multisensorial approach made possible by VR. However, while it has been known for decades that tactile stimulation is very efficient to relax users, reduce stress, and induce positive emotions, tactile stimuli are currently under-exploited in VR-based stress reduction interventions. This review focuses specifically on touch and its beneficial effects on stress and affect. Finally, we discuss and provide forward-looking perspectives on the present and future use of tactile stimulation as a component of VR tools designed to reduce stress.